Assessing Urban Vibrancy Level of Transit-Oriented Development Area in Lempuyangan Station, Yogyakarta - Haya Nabila Lelono; Dyah Titisari Widyastuti (Universitas Muhammadiyah Surakarta, 2026)
This study assesses the level of urban vibrancy within the Transit-Oriented Development (TOD) area of Lempuyangan Station, Yogyakarta, to evaluate how transit proximity contributes to the formation of an active and integrated urban environment. A quantitative spatial analysis is applied using a 400-meter TOD radius divided into 100 × 100 m grid cells to capture street-level dynamics. Urban vibrancy is measured through a composite index combining mixed-use diversity, morphological permeability, and concentration of people, represented by the Residential–Non-Residential Ratio (RNR), Building Mix Index (BuMi), intersection density, population density, and Point of Interest (POI) distribution. All indicators are normalized using min–max scaling and equally weighted to produce a vibrancy index ranging from 0 to 1. The results show a low weighted average index of 0.31, indicating that the TOD area is dominated by border vacuums (35.5%), formed by large monofunctional infrastructure that interrupts spatial continuity, while most of the area falls into potential vibrant zones (52.97%) where transit proximity exists but lacks sufficient density and functional diversity. Only 11.53% of the area reaches the vibrant category, appearing as small and fragmented active cores, and no grid achieves a very high level of vibrancy. These findings suggest that transit accessibility alone is insufficient to generate urban vibranacy due to monofunctional land use, low mix diversity, large impermeable blocks, and the spatial separation between residential concentration and activity centers. Strengthening vibrancy in the Lempuyangan TOD area therefore requires land-use diversification, increased development density, improved block permeability, and the transformation of inactive edges into active urban seams to create a more balanced and sustainable TOD environment.